2016
DOI: 10.1111/nmo.12768
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of AMPA receptor subunits within the enteric nervous system of the mouse colon and the effect of their activation on spontaneous colonic contractions

Abstract: Molecularly distinct AMPA receptor subtypes are differentially expressed within the neural networks of the mouse colon and have a direct role in motility. These data provide the rationale for the development of AMPA-selective ligands for the therapeutic delivery to the GIT in motility disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 59 publications
3
25
1
Order By: Relevance
“…GHB is a neurotransmitter found naturally at high levels in the intestine that inhibits intestinal peristalsis via GABA B receptors and has sedative effects in the CNS [70, 71]. Glutamate is an excitatory neurotransmitter in the enteric nervous system and in the brain where it also plays an important role in synaptic plasticity [72]. The posterior insula was also associated with abundance of a subunit of butyryl-CoA:acetate CoA-transferase, an enzyme used by intestinal bacteria such as Faecalibacterium in the final step of butyrate synthesis [73, 74].…”
Section: Discussionmentioning
confidence: 99%
“…GHB is a neurotransmitter found naturally at high levels in the intestine that inhibits intestinal peristalsis via GABA B receptors and has sedative effects in the CNS [70, 71]. Glutamate is an excitatory neurotransmitter in the enteric nervous system and in the brain where it also plays an important role in synaptic plasticity [72]. The posterior insula was also associated with abundance of a subunit of butyryl-CoA:acetate CoA-transferase, an enzyme used by intestinal bacteria such as Faecalibacterium in the final step of butyrate synthesis [73, 74].…”
Section: Discussionmentioning
confidence: 99%
“…Since DNQX also reduced electrically stimulated IJPs by 41% our data indicate a role for glutamate acting at AMPA receptors within local reflex pathways activated by L-amino acids. This is a significant and novel finding since many years of investigation have revealed little evidence demonstrating a physiological role for glutamate or its receptors despite their expression on several different types of enteric neurons in guinea pigs (Galligan, 1998 ; Kirchgessner, 2001 ), rats (Burns and Stephens, 1995 ), and mice (Seifi and Swinny, 2016 ). Liu et al ( 1997 ) showed that some myenteric AH and S neurons respond to glutamate via activation of AMPA and /or NMDA receptors indicating a possible role for glutamate in synaptic transmission within the myenteric plexus but studies demonstrating a functional role for glutamate are rare.…”
Section: Discussionmentioning
confidence: 99%
“…As a major excitatory neurotransmitter in CNS, Glu plays a fundamental role in the physiological condition [25]. Despite contentious topics in the literature and that exact pathways have not yet been fully elucidated, increasing evidences suggest that glutamate may also participate in the regulation of the GI motility, as well as in the brain-gut axis [25][26][27]. NL1 is localized to glutamatergic synapses and can bind to NX1 to target the formation and differentiation of glutamatergic synapses by clustering synaptic proteins such as NR1 and VGLUT1 [15,16].…”
Section: Discussionmentioning
confidence: 99%